User Perceptions of The Madrasah Aliyah Negeri (MAN) 1 Medan Library Related to Library Facilities and Infrastructure (Pena Cendekia Insani, 2023)
This study aims (1) to find out how the perception of users of the Madrasah Aliyah Negeri 1 Medan Library related to facilities and infrastructure, (2) to find out the obstacles faced by libraries in providing facilities and infrastructure (3) to find out the efforts made by libraries in provide facilities and infrastructure. The method used in this study uses a qualitative descriptive approach. Data collection techniques in this study through observation, interviews and documentation. The results of the research are user perceptions regarding the area of the room, reading tables and chairs, storage of goods, spatial planning, room decoration, collections, wifi and library computers still do not make users feel comfortable and have not been used optimally by library users. In addition, the obstacles faced by the library according to user perceptions can be seen from the facilities and infrastructure that are still inadequate to what is expected by library users. Efforts that have been made by the library in overcoming these obstacles are by submitting a proposal to the principal so that the facilities and infrastructure in the library are adequate and meet the needs of library users. In addition, the efforts made by the library are also through donations of books from students of MAN 1 Medan.